(untitled) (RuMoRes, 2010)
This article proposes a study on movie films Cidade de Deus, Gomorra [Gomorra] and Distrito 9 [District 9], pointing up three strategies of base (basic strategies) about passage, intermediation and restructuring processes, in which a “local” context exposes its own transformation into a “global” context on the contemporary audiovisual narratives that construct themselves according to the idea of “peripheral” (i.e. “on the outskirts”). We observe how those strategies are straightly associated with a current aesthetic experience, seemingly independent, insofar it no longer emerges from the social space, but from the mass media.